(E)-2-((E)-4-(2,6,6-trimethylcyclohex-1-en-1-yl)but-3-en-2-ylidene)hydrazine-1-carbothioamide C14H23N3S1 - Rong Zeng; Cong Huang; Yu-Fang Wu; Da-Yong Peng; Shang-Xing Chen (Zeitschrift für Kristallographie - New Crystal Structures)
[C14H23N3S1], monoclinic, P21/c (no. 14), a = 15.1642(8) Å, b = 6.9215(3) Å, c = 15.2182(7) Å, β = 112.675(2)°, V = 1473.83(12) Å3, Z = 4, R gt(F) = 0.0453, wR ref(F 2) = 0.1240, T = 296(2) K.